Analysis of thermocline development in the Persian Gulf - M. Ganj; S.M. Mosaddad (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
Thermocline is often observed in the open ocean and can be as a seasonal phenomenon in the shallower part of the ocean or as a permanent one that is usually seen in the deeper part of the open ocean. There are different forcing and climatic parameters that affect the thermocline development in the PG fromwinter to summer. These include tide, river inflow, solar radiation, evaporation, northwesterly wind and water exchange with the Oman Sea. Thermocline development that evolves from east to west is studied using numerical simulation and comparing the results with some existing observations. Results show that as the northwesterly wind in winter, at summer transition period, weakens the fresher inflow from Oman Sea can penetrate much further into the PG and the lake of wind lowers mixing which with stronger solar radiation lead to the near surface thermocline formation and its development from winter to summer even over the northwestern part of the PG. The analysis results show that for the more realistic monthly averaged wind experiments the thermocline develops as is indicated by summer observations. The results indicate that weaker winds and particularly stronger solar radiation in summer months can lead to an intense thermocline in the whole of the PG including in the northern part and vice versa for winter